2016
DOI: 10.1055/s-0036-1593533
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations of the ESSR Arthritis Subcommittee on Ultrasonography in Inflammatory Joint Disease

Abstract: This article presents the recommendations of the European Society of Musculoskeletal Radiology Arthritis Subcommittee on the use of ultrasonography (US) in rheumatic disease, focused on the examination of joints in the adult population. The recommended examination technique and protocols used in a radiologic work-up are discussed. The main US features that can lead to a final diagnosis in the most common rheumatic diseases are addressed. The differential diagnosis that should be considered at image interpretat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 34 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…Peripheral joints, synovial bursae, tendons, tendon sheaths and entheses are subject to evaluation (10,12) . At the initial stage of the disease, the thickening of the synovial membrane and, subsequently, its increased vascularization and effusion are observed.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral joints, synovial bursae, tendons, tendon sheaths and entheses are subject to evaluation (10,12) . At the initial stage of the disease, the thickening of the synovial membrane and, subsequently, its increased vascularization and effusion are observed.…”
Section: Discussionmentioning
confidence: 99%
“…The use of Doppler ultrasound may also yield useful information relating to the activity of inflammation in patients with known gout. 23 Ultrasound is however limited by both operator and patient factors and accuracy of the result is related to operator experience although studies have demonstrated good interobserver reliability for the detection of erosions and tophi among rheumatologists. 24 Ultrasound also depends on the availability of a suitable acoustic window, which may be limited in obese patients or in joints of the axial skeleton.…”
Section: Advanced Imagingmentioning
confidence: 99%